PROFESIONALISASI GURU MADRASAH ALIYAH DI KABUPATEN TANAH DATAR (Survei terhadap Proses Peningkatan Kemampuan Guru dalam Mencapai Kriteria Standar dalam Penampilannya sebagai Anggota Profesi Guru) - Gustina Gustina (Ta'dib, 2016)
AbstractThis research aims at investigating efforts done by teachers of Islamic Senior High Schools to improve their profesional competence. This research used descriptive quantitative research using survey approach. The population of this research was teachers of Islamic Senior High Shool in Tanah Datar. The sample were taken using sampling technique. The result of the research is as follows: (1) most of teachers fulfilled academic qualification; (2) some of teachers have high motivation to improve their competence by involving worskhops; (3) some of teachers participated in their concorcium to difficult several difficulties in teaching; (4) some teachers participated in several educational training to increase their competence. Kata Kunci: Profesionalisasi, kemampuan, kinerja guru madrasah.